Analysis of Islamic Marketing Ethics on Customer Loyalty with Customer Satisfaction as a Mediation (Survey of Visitors to Islamic-Themed Coffee Shops in Sukabumi City) - Ranti Nuraeni; Asep Muhamad Ramdan; Tetty Sufianty Zafar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the influence of Islamic marketing ethics on customer loyalty with customer satisfaction as a mediating variable, by surveying visitors to Islamic-themed coffee shops in Sukabumi City. This study uses a quantitative method with an associative descriptive approach. The sample used in this study was 135 respondents who were consumers who had visited or customers of Sono Space and Zenith Coffee Stores in Sukabumi City. Data were obtained through a distributed research questionnaire containing 27 questions regarding Islamic marketing ethics variables, customer satisfaction variables, and customer loyalty variables. Furthermore, the data obtained will be subjected to various tests such as validity and reliability tests using the help of smartPLS 3.0 software. The results of the study show that the Islamic marketing ethics variable on customer satisfaction is tested significant, the customer satisfaction variable on customer loyalty, the Islamic marketing ethics variable on customer loyalty shows positive and significant and the customer satisfaction variable mediates effectively in the relationship between the Islamic marketing ethics variable and the customer loyalty variable is tested significant.